2022
DOI: 10.2174/1573405617666210712141600
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Liver Protections Against Lipotoxicity and Oxidative Stress to Avoid the Progression of Non-alcoholic Fatty Liver to more Serious Disease

Abstract: : Non-alcoholic fatty liver disease (NAFLD) is a metabolic disorder characterized by an ectopic accumulation of lipids in at least 5% of hepatocytes. The first phase of the disease, called hepatic steatosis, progresses over time to chronic conditions such as steatohepatitis, cirrhosis, and hepatic insufficiency and cancer. The accumulation of free fatty acids in hepatocytes, particularly saturated fatty acids, is a key process in the development and progression of NAFLD. Furthermore, the accumulation of oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hepatic steatosis is the initial stage of NAFLD, which is a metabolic disorder characterized by ectopic accumulation of lipids in liver cells (Barrios-Maya et al, 2022). N-3 PUFAs played an important role in regulating fat accumulation and fat elimination in the liver, and the disorder of n-6/n-3 PUFA ratio in the liver affected the histological pattern by regulating the amount of liver lipids (El-Badry et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic steatosis is the initial stage of NAFLD, which is a metabolic disorder characterized by ectopic accumulation of lipids in liver cells (Barrios-Maya et al, 2022). N-3 PUFAs played an important role in regulating fat accumulation and fat elimination in the liver, and the disorder of n-6/n-3 PUFA ratio in the liver affected the histological pattern by regulating the amount of liver lipids (El-Badry et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that lipotoxicity correlates with the production of toxic lipid metabolites, such as ceramides, lysophosphatidylcholine, diacylglycerol and metabolites of cholesterol [39,40]. At the same time, lipotoxicity triggers the oxidative stress process and the production of reactive oxygen species (ROS), which alters mitochondrial function [41,42]. Mitochondrial dysfunction decreases ATP production and further increases the accumulation of toxic lipid intermediates, which accentuate the production of ROS and cell death mechanisms [32,40].…”
Section: Lipid Metabolism and Its Implications In The Steatosis Processmentioning
confidence: 99%